Accounting curriculum and market needs. Issue 8 (4th November 2014) - Mandilas, Athanasios; Kourtidis, Dimitrios; Petasakis, Yiannis
Abstract : Purpose: – The purpose of this paper is to examine whether the accounting curriculum fits business demand. More specifically, it determines competencies that Greek companies demand from higher education[1] graduates and addresses any mismatches between the market's needs and the academic accounting/business curriculum through a survey in Greece. Design/methodology/approach: – Using a survey to reveal their perceptions' differences, the sample included 166 students, 25 lecturers/professors from a department of Accounting and Finance (Higher Education) and 155 companies. Findings: – The results provide evidence that all these groups have different perceptions of the curriculum. Practical implications: – The study suggests ways to improve the academic accounting curriculum. Originality/value: – To the best of the authors knowledge, there is not any previous study that examines these parameters in Greece.